2017
DOI: 10.1111/jgh.13822
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer bleeding patients with Rockall scores ≥6 are at risk of long‐term ulcer rebleeding: A 3.5‐year prospective longitudinal study

Abstract: Background and Aim: Patients with high Rockall scores have increased risk of rebleeding and mortality within 30 days after peptic ulcer bleeding, but long-term outcomes deserve follow-up after cessation of proton pump inhibitors. The paper aimed to validate whether patients with high Rockall scores have more recurrent ulcer bleeding in a 3.5-year longitudinal cohort. Methods: Between August 2011 and July 2014, 368 patients with peptic ulcer bleeding were prospectively enrolled after endoscopic hemostasis to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…All participants were consecutively assessed for eligibility and enrolled from August of 2011 to July of 2016 after signing an informed consent. This study extended our original database to prove our hypothesis and was one of the studies analyzing the short-term and long-term outcomes in bleeding peptic ulcer populations based on our database [11][12][13][14].…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…All participants were consecutively assessed for eligibility and enrolled from August of 2011 to July of 2016 after signing an informed consent. This study extended our original database to prove our hypothesis and was one of the studies analyzing the short-term and long-term outcomes in bleeding peptic ulcer populations based on our database [11][12][13][14].…”
Section: Methodsmentioning
confidence: 86%
“…The criteria of the Forrest classification [2,3] and the Rockall score [7] a We modified the diagnostic criteria of comorbidities as follows to make this variable clearer to be scored than it was according to the old criteria b Cardiac failure included congestive heart failure with New York Heart Association Function I to IV c Any major comorbidity included lung disease (chronic obstructive pulmonary disease, pulmonary tuberculosis, pneumonia, or empyema), chronic kidney disease stage III (estimated glomerular filtration rates between 30 and 60 mL/min/1.73 m 2 ), rheumatoid arthritis, sepsis, newonset cerebrovascular accident, intensive care unit stay, mechanical ventilator support for > 24 h, or any major surgery (on the central nervous system, thorax, abdomen, long bones or spinal bones) within 14 days prior to bleeding d Liver failure included liver cirrhosis, Child-Pugh A, B, or C e Renal failure included chronic kidney disease stage IV (estimated glomerular filtration rates between 15 and 30 mL/min/1.73 m 2 ), stage V (estimated glomerular filtration rates < 15 mL/min/1.73 m 2 ) with or without maintenance dialysis, or acute kidney injury with estimated glomerular filtration rates < 30 mL/min/1.73 m 2 Previous studies have shown that comorbid patients have impaired tissue healing on peptic ulcers [8][9][10]. Studies have also shown that patients' Rockall scores are often ≥ 6 in those with comorbidities, who also exhibit an increased risk of recurrent peptic ulcer bleeding [11,12]. Therefore, we propose that patients with Rockall scores ≥ 6 are still at risk of recurrent bleeding after initial treatment partially because of impaired tissue healing, which results in delayed fading out of the Forrest lesions.…”
Section: Tablementioning
confidence: 99%
“…A 3.5-year prospective longitudinal study revealed that re-bleeding during the follow-up period was higher in patients with the Rockall score 2. Additional independent risk factors included disturbances of the clotting system and ASA physical status class [ 31 ]. The full Rockall score is better for 1-month mortality prediction while the Glasgow-Blatchford system is better for predicting other outcomes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Rockall scores ≥ 6 to define patients who were at high risk of rebleeding [6][7][8][9]. The parameters of the Rockall score are listed in Supplementary Table 1 and the definitions for the co-morbidities in the score were listed in previous studies in more detail [6,9].…”
Section: The Characteristics Of Participantsmentioning
confidence: 99%
“…The Rockall score contains five parameters with total scores from 0 to 11, including age, shock, comorbidity, endoscopic diagnosis, and endoscopic evidence of bleeding (Supplementary Table 1) [6,7]. Previous studies showed that patients with Rockall scores ≥6 had an increased risk of short-term and long-term recurrent ulcer bleeding [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%